The difference that black female judges in South Africa make - Chiseya, Tipei Wadzanai (Centre for Law and Society, 2026)
Historically in South Africa women as a group faced many obstacles in entering the legal • profession.1 • Although in 1923 an established law was enacted allowing women to be admitted into legal practice gender bias was still a barrier to their admission'. 2 Women bore . the brunt of gender discrimination but black women in particular felt it the most. Their identity as black women together with the psychological, social and cultural experiences they . have endured in the past makes them distinct as a group. Issues of race and gender inequality are currently still rife within the legal profession. Thus, there is need to address such issues. • At present the statistics of the total number of judges presiding over our higher courts shows • that out of the 235 judges only 55 are women (that is only 23 per cent of the overall judges). There is need to increase the number of females particularly black female judges in order to • achieve a diverse judiciary. This thesis focuses on the difference in experiences that is encapsulated from the background of ( a sample) six black women judges and how such experiences impact on their decisions. This study also seeks to address the issue of judicial transformation in South Africa. A diverse. judiciary is something we should care about. Ensuring that equal numbers of race, class and gender are represented on the bench is fundamental to our constitutional democracy.